2015
DOI: 10.1002/aur.1584
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity and specificity of the social communication questionnaire for autism spectrum with respect to age

Abstract: The age neutrality of the Social Communication Questionnaire (SCQ) was examined as a common screener for ASD. Mixed findings have been reported regarding the recommended cutoff score's ability to accurately classify an individual as at-risk for autism spectrum disorder (ASD) (sensitivity) versus accurately classifying an individual as not at-risk for ASD (specificity). With a sample from the National Database for Autism Research, this study examined the SCQ's sensitivity versus specificity. Analyses indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 41 publications
5
40
0
Order By: Relevance
“…Although the SCQ is an appropriate screening measure for autism and for individuals with intellectual disabilities, questions were not adapted within the current investigation to represent the ageing sample. Literature suggests the potential benefits of modifying questions and subsequent cutoff scores to reflect samples [62]. Future research should therefore attempt to adapt questions to ensure accuracy of responses whilst maintaining the specificity of the measure.…”
Section: Limitationsmentioning
confidence: 99%
“…Although the SCQ is an appropriate screening measure for autism and for individuals with intellectual disabilities, questions were not adapted within the current investigation to represent the ageing sample. Literature suggests the potential benefits of modifying questions and subsequent cutoff scores to reflect samples [62]. Future research should therefore attempt to adapt questions to ensure accuracy of responses whilst maintaining the specificity of the measure.…”
Section: Limitationsmentioning
confidence: 99%
“…It has been noted that the SCQ may be better at identifying children over seven years, than younger ones [Corsello et al, 2007;Norris & Lecalvalier, 2010]. For younger (<4 years) children, studies have found that an SCQ score of 11 maximizes sensitivity and specificity [Allen et al, 2007;Barnard-Brak, Brewer, Chesnut, Richman, & Schaeffer, 2016;Lee, David, Rusyniak, Landa, & Newschaffer, 2007;Wiggins et al, 2007]. Although these studies indicate child age can impact the performance of the SCQ, there is less evidence about how other demographic characteristics of children and parents may influence the SCQ score.…”
mentioning
confidence: 99%
“…Confirmation of the ASC diagnosis was provided by the SCQ, which was completed by a caregiver. The average SCQ score was 23.4 (SD = 4.64), i.e., higher than the cut-off score of 15 (see Barnard-Brak et al (2016) for a discussion about cut-off scores for the SCQ regarding sensitivity…”
Section: Participantsmentioning
confidence: 90%